2008
DOI: 10.1007/s00417-008-0878-4
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of experimental retinal vein occlusion in rabbit; arterial occlusion following venous photothrombosis

Abstract: RVO in rabbits has a different course than in human and it can be classified into three stages. At stage 1 (the first few days after laser photothrombosis), there is a retrograde propagation of the blood clot in the retinal veins that extends to the retinal arteries and choriocapillaries. As a result, there is no retinal blood flow at this stage in most cases. At stage 2 (between weeks 1 and 3), partial or complete revascularization occurs but the vessels have an abnormal pattern. At stage 3 (after week 3) no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 16 publications
3
38
0
Order By: Relevance
“…16 The point is that the transient elevation of the VEGF protein level just after the photocoagulation can be suppressed by medical drugs, and Although the retinal vessels of rabbits have some anatomical differences when compared with those of humans, 17 the pathological effects of the rabbit RVO model is expected to be similar to humans. 9 If the findings in our data using experimental models are confirmed in humans, a better way to treat vascular pathology of retina would be set in clinical practice. However, we are not able to obtain the retinal or choroidal tissue from the patients with vein occlusion.…”
Section: -6mentioning
confidence: 96%
See 2 more Smart Citations
“…16 The point is that the transient elevation of the VEGF protein level just after the photocoagulation can be suppressed by medical drugs, and Although the retinal vessels of rabbits have some anatomical differences when compared with those of humans, 17 the pathological effects of the rabbit RVO model is expected to be similar to humans. 9 If the findings in our data using experimental models are confirmed in humans, a better way to treat vascular pathology of retina would be set in clinical practice. However, we are not able to obtain the retinal or choroidal tissue from the patients with vein occlusion.…”
Section: -6mentioning
confidence: 96%
“…Optical coherence tomography, which provides a crosssectional retinal image with high resolution, is used for not only clinical examination but also the experiments using animal models. 9,[18][19][20] However, it was difficult for us to detect a subtle change of retinal tissue after the venous occlusion (data not shown). In this study, therefore, we could not get more detailed findings using optical coherence tomography than histological examination and in situ hybridization.…”
Section: -6mentioning
confidence: 99%
See 1 more Smart Citation
“…Though laser-induced retinal vein occlusion is a common experimental model of CRVO, there are some differences to clinical conditions. One limitation of the model is the tendency to spontaneous recanalization [22,23]. Therefore, only tissues from animals, in which CRVO was confirmed in fluorescein angiography before the animals were killed, were used for the PCR analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al indicated that in laser-induced RVO in rat models, significant ganglion cell layer cell loss is associated with the pathogenesis of RVO [134]. On the other hand, Ameri et al suggested that the natural course of experimentally created RVO in rabbits was different from that in human [135]. Thus, it still seems to be difficult to obtain the basic evidence for the neuroprotective therapies for RGC death in RVO.…”
Section: Challenge To Neuroprotective Therapies For Dr and Rvomentioning
confidence: 91%